SIFAT FISIS DAN MEKANIKA, WETABILITAS DAN EMISI FORMALDEHIDA BAMBU LAMINA YANG DIBUAT DARI BEBERAPA JENIS BAMBU - M. Loiwatu (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
Laminating technology is one of technique to utilize thick pieces of bamboo becoming composite product that might be replace solid wood. Objective laminating technique is to make original size of resources become bigger in term of length, width and thickness. Laminated product was made by binding of two or more pieces plane wood in parallel grain using adhesives and press to increase its strength and quality. Objective of the study was To determine moisture content and specific gravity of laminated bamboo, to determine modulus of elasticity (MOE), modulus of rupture (MOR), compressive strength, shear strength and percentage of rupture of laminated bamboo, To determine wet ability of bamboo, To determine emission of formaldehyde release from laminated bamboo that utilize urea formaldehyde as binding agent, To determine amount of delaminating of laminated bamboo and viscosity of adhesives. Result of the study indicated that preliminary treatment (A), and level of cold press (C) was significant effect to the properties of laminated bamboo, although type of adhesives was not significant effect to the properties as single factor. Interaction factors such as AB, AC and BC was significant effect to the properties of laminated bamboo, although combination factor such as ABC was not significant. Preliminary treatment was significant effect to the specific gravity of laminated bamboo that made of petung, jawa and kuning bamboo; modulus of elasticity (MOE) of laminated bamboo that made of suanggi bamboo; compression strength of laminated bamboo made of petung and suanggi bamboo. Another hand, level of cold press was significant effect to the modulus elasticity (MOE) of laminated bamboo, made of petung bamboo; and percentage of rupture of laminated bamboo made of petung, jawa and suanggi bamboo.